Science-Based TV Spots: Educating the Public About Forestry - Jeffrey C. Hino; Edward C. Jensen (Journal of Applied Communications, 1996)
A cooperative effort between a state educational agency and a college of forestry applied the power of public opinion research, the reach of broadcast television, and the full resources of an internationally recognized forestry research institution to inform the public about important forest resource issues.